RFG Presentation No. 1 (2022) - López de Castro, Sandra (Revista Arbitrada Formación Gerencial, 2024)
The refereed management training magazine is pleased to present the first issue of the 21st year of the magazine, corresponding to May 2022. From the Magazine, we want to become a support for researchers who continue to be active despite the difficulties, contributing to the publication and dissemination of their research and the contributions they make to the solution of social problems and the construction of theories that contribute to the advancement of management and humanistic sciences.